Direction of Trade Statistics, June 2018. (Direction of Trade Statistics; Direction of Trade Statistics ;, 2018)
This quarterly issue of Direction of Trade Statistics (DOTS) provides, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. The yearbook and quarterly issues of the DOTS publication provide tables with current reported data (or estimates) on the value of merchandise trade statistics (exports and imports) by partner country for all IMF members. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The yearbook provides, for the most recent seven years, detailed trade data by country for approximately 184 countries, the world, and major areas. Other countries may report monthly data that are less current, or the information may be compiled and made available in quarterly or annual frequency. For some countries, the data reported to the United Nations Statistical Division also have been used. Estimation occurs if a reporting country does not report trade with its partners for a specific period. In order to provide guidance regarding the sources of the figures for individual countries, figures in the country, world, and area pages are shown with symbols to the right of the figure.